Association between dietary nutrient intake and sleep disorders in hypertensive patients: a cross-sectional study of NHANES, 2005–2020 - Tian, Aokai; Zheng, Yafang; Jin, Jing; Huang, Chunyuan (Frontiers in Nutrition, 2025)
BackgroundDietary nutrient intake is critical for healthy sleep patterns, but studies in hypertensive patients are lacking. This study examines the connection between hypertension patients’ and their dietary nutrient intake.MethodsAdults with complete data on hypertension, dietary nutrient intake, and sleep disorders from the 2005 to 2020 National Health and Nutrition Examination Survey (NHANES) were used. The association between dietary nutrient intake and sleep disorders in hypertensive patients was assessed by multivariable logistic regression, smoothed curve fitting, subgroup analyses, interaction tests, and threshold effect analyses.ResultsThere were altogether 15,871 subjects included in this work, with 5,791 individuals presenting with sleep disorders. The positive associations of dietary sugar, fat, and calcium intake with sleep disorders remained stable in fully adjusted models. Analyses of subgroups indicated that the link between sugar consumption and sleep disorders was affected by both gender and diabetes, while the connection between fat consumption and sleep disorders was influenced by gender alone. In female patients, a U-shaped association was observed between dietary sugar, fat intake, and sleep disorders, with inflection points of 140 and 66, respectively. Finally, the relationships between dietary sugar, fat, and calcium intake and various types of sleep disorders were further analyzed. The findings indicated that the intake of dietary sugar was correlated with other types of sleep, and dietary calcium intake was correlated with restless legs syndrome.ConclusionOur results indicate that the increased risk of sleep disorders in hypertensive patients may be associated with increased dietary sugar, fat, and calcium intake.